1995
DOI: 10.1007/bf03401557
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and In Vivo Efficacy of Recombinant Plasmodium falciparum Merozoite Surface Protein-1 in Aotus Monkeys

Abstract: Vaccination of A. nancymai with yMSP1(19) induced protective immune responses. The course of recrudescing parasitemias in protected monkeys suggested that immunity is not mediated by antibodies that block invasion. Our data indicate that vaccine trials with the highly adapted FVO strain of P. falciparum can be tested in A. nancymai and that MSP1(19) is a promising anti-blood-stage vaccine for human trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
288
3
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(302 citation statements)
references
References 18 publications
9
288
3
1
Order By: Relevance
“…[7][8][9][10][11] A small number of heterologous challenges have been performed in the past using P. falciparum strains in Aotus monkeys. These studies, performed in other species of Aotus, also showed that previous infection provided protection from subsequent challenge with the same strain.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] A small number of heterologous challenges have been performed in the past using P. falciparum strains in Aotus monkeys. These studies, performed in other species of Aotus, also showed that previous infection provided protection from subsequent challenge with the same strain.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Several other molecules are being channelled into human trials on the basis of results considered promising and obtained in one of the primate, mouse, or in-vitro models (figure 1). [39][40][41][42][43] Clinical trials will be essential to show whether these results can be extended to human beings.…”
Section: Personal Viewmentioning
confidence: 99%
“…Parts of MSP1, and in particular the C-terminal region have been produced in various expression systems [7]. Immunization of nonhuman primates using various preparations of recombinant MSP1 19 and MSP1 42 led to inconsistent results in terms of protection against a live-parasite challenge ( [7][8][9][10][11] Kaslow et al, unpublished data; Longacre et al, unpublished data).…”
Section: Introductionmentioning
confidence: 99%